Taking Into Account Physical Fitness for Middle-Aged Men Aged 45-60 Develop a Health Exercise Collection (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the development of a set of health-improving exercises for middle-aged men aged 45-60, taking into account physical fitness. A healthy lifestyle should include the implementation of methods for restoring mental and physical performance. For people of the first period of mature age, the tasks of physical education are to further increase the level of physical culture, deepen knowledge about physical training, form a stable motivation for systematic physical exercises, both sports and recreational.